State Finance During the Caliphate of Mu’awiya - Batayneh, Muhammad D. Batayneh (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
State Finance During the Caliphate of Mu’awiya